Job Insecurity: Toward Conceptual Clarity - Greenhalgh, Leonard; Rosenblatt, Zehava (Academy of Management Review, 1984)
A model is presented that summarizes existing knowledge concerning job insecurity, points at its deficiencies, and identifies further research needed to understand the nature, causes, and consequences of this increasingly important phenomenon. Such knowledge is crucial because job insecurity is a key element in a positive feedback loop that accelerates organizational decline.